Understanding the Fourth Gospel. Second Edition. By John Ashton - Moody Smith, D. (The journal of theological studies, 2008)
The second edition of Ashton's magnum opus was prompted by an invitation to participate in the November 2007 (San Diego) meeting of the Society of Biblical Literature. There he presented ‘Second Thoughts on the Fourth Gospel’, which is now the lead article in the already published volume, What We Have Heard from the Beginning: The Past, Present, and Future of Johannine Scholarship, edited by Tom Thatcher (Baylor: Baylor University Press, 2007). Ashton's succinct account of the nature of the revision may be found there and in the first couple of pages of the book itself., Readers familiar with the original (1991) edition will see that Ashton adheres to the same basic positions. Yet there have been significant changes, both deletions and additions, and one chapter has been transposed.